(untitled) (Journal of Civil Engineering Researchers, 2022)
Reinforced concrete columns to steel beam connections are recently considered as structural system. This system takes the advantages of both through optimally combining metal and concrete structural elements. There are two connections through beam and through column connections. This study first reviewed the literature; then, the authors modeled a sample connection experimentally carried out in a laboratory by Cheng Chih and Cheng Tung Chen in 2005 by ABAQUS finite element software and investigated seismic performance of RCS connections under back/forward and monotonic loadings. Once the finite element model was validated, a parametric study (studying web steel panel thickness at the joint, studying coating thickness, etc.) was conducted; and finally, a modified model was proposed following connection results were compared showing a more stable and desired behavior in addition to the increased capacity of the connections. The result showed that the use of a through-plate with shear keys in the joint zone will increase the strength of the joint and the formation of a plastic joint outside the joint and will greatly improve the joint behavior. So that the contribution of concrete in the shear capacity of this area has increased, which was 73% for the modified model of Cheng and Chen. Also the use of a through-plate for RCS joints converts the forces transmitted from the beam to in-plane stresses and by shear keys, through two shear and support mechanisms, these forces are transferred to the concrete of the joint area and in consequence, these stresses are transferred to the concrete column.